2019
DOI: 10.21577/1984-6835.20190019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Micro-Crack Incidence and their Influence on the Corrosion Resistance of Steel Coated with Different Chromium Thicknesses

Abstract: Avaliação da Incidência de Micro Trincas e suas Influências na Resistência à Corrosão do Aço Revestido com Diferentes Espessuras de Cromo Resumo: Revestimentos de cromo são frequentemente utilizados para aplicação onde a corrosão e desgaste estão combinados. O objetivo deste trabalho foi avaliar a incidência de micro trincas e a resistência a corrosão por pites de cinco diferentes espessuras de revestimento de cromo aplicadas sobre o aço C45K. Estes revestimentos de cromo foram aplicados através do processo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…It is known that naturally, with the help of the solar energy, electrolysis occurs in plants and algae. In industry, electrolysis is performed to clean and preserve metallic objects from corrosion, while in the future even hydrogen might be produced by electrolysis as an alternative to fossil fuel (Santos et al, 2019;Rashid, Al Mesfer, Naseem, & Danish, 2015). Meanwhile, some people believe that electrolysis makes water better and that drinking it may cure many different illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that naturally, with the help of the solar energy, electrolysis occurs in plants and algae. In industry, electrolysis is performed to clean and preserve metallic objects from corrosion, while in the future even hydrogen might be produced by electrolysis as an alternative to fossil fuel (Santos et al, 2019;Rashid, Al Mesfer, Naseem, & Danish, 2015). Meanwhile, some people believe that electrolysis makes water better and that drinking it may cure many different illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…The low electrochemical performance observed by C1, in comparison with C2 for instance, might be addressed by the amount of uncovered substrate seen through the SEM magnifications in Figure 7. Some works reported that uncovered sites of steel in a surface with huge precipitation of corrosion products, such as FeCO 3 , might lead to an acceleration in the iron dissolution by the occurrence of a galvanic couple increased by the presence of great cathodic sites (iron carbonate structures) alongside small anodic spots (uncovered steel) [24,32,43]. This latter behaviour also might be the cause of the low capacitive feature at low frequencies on EIS analysis (Figures 3 and 4) for condition C2 (120°C, absence of HAc) [44].…”
Section: Temperature Influencementioning
confidence: 99%